Personal Branding Analysis of Bengkulu City Selebgram Through Ikoy-Ikoy Content - Nur Leli; Sri Narti; Anis Endang SM (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
This study aims to determine the personal branding of Bengkulu City celebgram through ikoy-ikoy content. This study used data collection techniques of observation, interviews, and documentation. The subject in this study was@akadika. This research is qualitative with a descriptive approach with the theory of Personal Branding called Montoya (in Haroen 2014) consisting of eight personal branding concepts. The results of this study show that the Akadika program fulfills eight personal branding concepts, namely: 1) Specialization: Akadika with his expertise in photography distributes Ikoy-Ikoy in the form of color presets. 2) Leadership: Akadika explained by asking questions about photography, either from the color presets used, the equipment, or the settings used. 3) Personality: Akadika makes good use of its brand so that it can be trusted by the followers by posting content that can add insight. 4) Difference: Akadika is better known as a photographer with the abilities possessed by him. 5) Visible: to be more recognizable and visible, Akadika is always active on Instagram social media by posting educational content and providing photos and videos. 6) Unity: Akadika's life on social media Instagram describes how his life in the real world looks like. 7) Constancy: the steps taken by Akadika in providing Ikoy-Ikoy content are making questions, where in the question there is an image that explains the question. 8) Good Name: by providing Ikoy-Ikoy content, it can broaden the horizons of its followers on Instagram and get the color presets they share